The Analysis of Flouting Maxim in Cinderella Movie - Khofifah, Sonya; Marantika, I Made Yogi (Journal of Language and Applied Linguistics, 2024)
The purposes of this study are to find out the types of flouting maxim found in Cinderella movie and the context situations influence the interpretation of flouting in the Cinderella movie. The researcher used the theory t proposed by Grice in his book (1975) to analyze the types of flouting maxims in Cinderella movie and the theory of the context of situation by Halliday and Hassan (1985). The method that used in this research is descriptive qualitative research. The results show that in Cinderella movie, the characters flout all the maxims with 20 data of flouting. Those are: Flouting Maxim of Quantity 7 data (35%), Flouting Maxim of Quality 2 data (10%), Flouting Maxim of Relevance 5 data (25%) and Flouting Maxim of Manner 6 data (30%). From those forms, Flouting Maxim of Quantity has the highest occurrences used among others. The characters in this movie mostly flouted the maxim of quantity to strengthen their opinion. They were giving too much or less information to the listener or more unnecessary one. Moreover, It also would create inexplicable statement to be uttered in some particular situations which could not be understood by the listener.